The color line a novel - Scego, Igiaba 1974- (Other Press, 2022)
"Inspired by true events, this gorgeous, haunting novel intertwines the lives of two Black female artists more than a century apart, both outsiders in Italy. It was the middle of the nineteenth century when Lafanu Brown audaciously decided to become an artist. In the wake of the American Civil War, life was especially tough for Black women, but she didn't let that stop her. The daughter of a Chippewa woman and an African-Haitian man, Lafanu had the rare opportunity to study, travel, and follow her dreams, thanks to her indomitable spirit, but not without facing intolerance and violence. Now, in 1887, living in Rome as one of the city's most established painters, she is ready to tell her fiancé about her difficult life, which began in a poor family forty years earlier. In 2019, an Italian art curator of Somali origin is desperately trying to bring to Europe her younger cousin, who is only sixteen and has already tried to reach Italy on a long, treacherous journey. While organizing an art exhibition that will combine the paintings of Lafanu Brown with the artworks of young migrants, the curator becomes more and more obsessed with the life and secrets of the nineteenth-century painter. Weaving together these two vibrant voices, Igiaba Scego has crafted a powerful exploration of what it means to be "other," to be a woman, and particularly a Black woman, in a foreign country, yesterday and today"--
Keywords: African American women artists / Italy / 19th century / Fiction; Race discrimination / Italy / Rome / 19th century / Fiction; Multiracial people / 19th century / Fiction; Race relations / Fiction; Rome (Italy) / History / 19th century / Fiction; Femmes artistes noires américaines / Italie / 19e siècle / Romans, nouvelles, etc; Discrimination raciale / Italie / Rome / 19e siècle / Romans, nouvelles, etc; Rome (Italie) / Histoire / 19e siècle / Romans, nouvelles, etc; Fictional Work; Novels; Romans